Equação de referência para ventilação voluntária máxima em crianças e adolescentes - Silva, Jaksoel Cunha (2017)
Introduction: The individual's ability to sustain high ventilatory demand can be tested with the maximal voluntary ventilation (VVM) maneuver. Objectives: To develop a reference equation for maximum voluntary ventilation in children and adolescents in the Brazilian population and to test the validity of the developed equations. Methods: A total of 348 healthy volunteers, 6 to 17 years old, 248 individuals to develop the reference equation and 100 individuals were tested to test the validity of the developed equations. Volunteers with abnormal lung function (<80% prev) or history of acute or chronic respiratory disease were excluded. Pulmonary function was assessed by spirometry and maximum voluntary ventilation (VVM). Results: The predictive variables FEV1 and PEF explained 68% of the variance in VVM in children and FEV1, PEF, age and gender explained 51% in adolescents. There was a difference in VVM between girls and boys only after 12 years of age. There was no significant difference between the values of VVM measured and predicted for children (64 ± 10 vs 64 ± 8 L / min) and adolescents (111 ± 23 vs 113 ± 22 L / min). The ICC (95% CI) presented excellent reliability (0.95 [0.91 - 0.97] vs 0.90 [0.82 - 0.94]), and the Bland-Altman analysis showed bias = - 0.8, with agreement limits of 11 a - 12 L / min for children and bias = -2.7, with agreement limits of 17 to -22 L / min for adolescents. Conclusion: Reference equations were established for VVM in adolescent children in the Brazilian population, as well as their validity.